Water, Energy, and Waste Services - Marco Ranzato; Luisa Moretto (Revue Internationale des Études du Développement)
The sustainable provision and access to water, energy, and waste services in urban areas are now being explored both as service coproduction and as an urban commons. This article aims at linking the reflection on these two streams of literature by investigating how the coproduction of urban water, energy, and waste services in the Global South can inform the reflection on the urban commons. The emphasis is on the spatiality and governance features attached to polycentrism, a concept key both to coproduction and commons.